1994
DOI: 10.1152/ajpregu.1994.267.6.r1528
|View full text |Cite
|
Sign up to set email alerts
|

Blood and brain temperatures of free-ranging black wildebeest in their natural environment

Abstract: Using miniature data loggers, we measured the temperatures of carotid blood and brain in four wildebeest (Connochaetes gnou) every 2 min for 3 wk and every 5 min, in two of the animals, for a further 6 wk. The animals ranged freely in their natural habitat, in which there was no shelter. They were subject to intense radiant heat (maximum approximately 1,000 W/m2) during the day. Arterial blood temperature showed a circadian rhythm with low amplitude (< 1 degree C) and peaked in early evening. Brain temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 0 publications
5
65
5
Order By: Relevance
“…The zebras exhibited a biphasic nychthemeral rhythm of blood temperature, with a mean amplitude of •1.7°C, around a mode of •38°C. This oscillation in blood temperature was greater than that measured in free-ranging black wildebeest (Jessen et al 1994) and springbok (Mitchell et al 1997), but similar to the variation in rectal temperature previously reported in tame donkeys exposed to natural environmental variables (SchmidtNielsen et al 1957;Yousef & Dill, 1969). In donkeys, rectal temperature closely tracked the prevailing globe temperature, reaching a minimum between 24.00 and 04.00 h, and a maximum at 12.00 h (Yousef & Dill, 1969).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The zebras exhibited a biphasic nychthemeral rhythm of blood temperature, with a mean amplitude of •1.7°C, around a mode of •38°C. This oscillation in blood temperature was greater than that measured in free-ranging black wildebeest (Jessen et al 1994) and springbok (Mitchell et al 1997), but similar to the variation in rectal temperature previously reported in tame donkeys exposed to natural environmental variables (SchmidtNielsen et al 1957;Yousef & Dill, 1969). In donkeys, rectal temperature closely tracked the prevailing globe temperature, reaching a minimum between 24.00 and 04.00 h, and a maximum at 12.00 h (Yousef & Dill, 1969).…”
Section: Discussionsupporting
confidence: 82%
“…Our measurements on zebra add a fourth species, and the first perissodactyl, to our studies of ungulates, which previously included black wildebeest (Jessen et al 1994), springbok (Mitchell et al 1997) and eland (Fuller et al 1999a); these four studies remain the only continuous measurements of brain and arterial blood temperatures in free-ranging animals in their natural habitat. Our new study was the first to measure brain and blood temperatures in a free-ranging mammal that does not have a carotid rete, the anatomical structure usually associated with selective brain cooling.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations